Characterization of Neck Strength in Healthy Young Adults. Issue 9 (5th February 2017) - Catenaccio, Eva; Mu, Weiya; Kaplan, Atira; Fleysher, Roman; Kim, Namhee; Bachrach, Tamar; Zughaft Sears, Malka; Jaspan, Oren; Caccese, Jaclyn; Kim, Mimi; Wagshul, Mark; Stewart, Walter F.; et al.
Abstract: Background: The role of cervical muscle (neck) strength in traumatic brain and spine injury and chronic neck pain disorders is an area of active research. Characterization of the normal ranges of neck strength in healthy young adults is essential to designing future investigations of how strength may act as a modifier for risk and progression in head and neck disorders. Objective: To develop a normative reference database of neck strength in a healthy young adult population, and to evaluate the relationship of neck strength to anthropometric measurements. Design: Cross‐sectional. Setting: An academic medical center research institution. Participants: A total of 157 healthy young adults (18‐35 years of age) had their neck strength measured with fixed frame dynamometry (FFD) during 1 visit to establish a normative neck strength database. Interventions: Not applicable. Main Outcome Measurements: Peak and average strength of the neck muscles were measured in extension, forward flexion, and right and left lateral flexion using FFD. The ranges of peak and average neck strength were characterized and correlated with anthropometric characteristics. Results: In all, 157 subjects (84 male, 73 female; average age 27 years) were included in the normative sample. Neck strength ranged from 38 to 383 Newtons in men and from 15 to 223 Newtons in women. Normative data are provided for each gender in all 4 directions. Weight, body mass index, neck circumference, and estimated neck muscle volume were modestly correlated with neck strength in multiple directions (correlation coefficients < .4). In a multivariate regression model, weight in women and neck volume in men were significant predictors of neck strength. Conclusions: Neck strength in healthy young adults exhibits a broad range, is significantly different in men from that in women, and correlates only modestly with anthropometric characteristics. Level of Evidence: Not applicable.